2006
DOI: 10.1007/s00535-006-1880-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in plasma ghrelin levels, gastric ghrelin production, and body weight after Helicobacter pylori cure

Abstract: Changes in plasma ghrelin concentrations before and after H. pylori cure were inversely correlated with body weight change and initial plasma ghrelin levels but not with gastric ghrelin production in Japanese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 38 publications
4
45
1
Order By: Relevance
“…Together, these observations suggest that ghrelin levels respond in a compensatory fashion to bidirectional alterations in body weight, consistent with the hypothesis that ghrelin contributes to the known adaptive metabolic responses to such alterations (51). Yet, in agreement with our data, Osawa et al recently showed that mean plasma ghrelin concentrations significantly decreased after successful H. pylori treatment, though with wide variation (48). In that report, changes in plasma ghrelin concentrations before and 12 weeks after H. pylori cure were inversely correlated with body weight change but not with gastric ghrelin production.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Together, these observations suggest that ghrelin levels respond in a compensatory fashion to bidirectional alterations in body weight, consistent with the hypothesis that ghrelin contributes to the known adaptive metabolic responses to such alterations (51). Yet, in agreement with our data, Osawa et al recently showed that mean plasma ghrelin concentrations significantly decreased after successful H. pylori treatment, though with wide variation (48). In that report, changes in plasma ghrelin concentrations before and 12 weeks after H. pylori cure were inversely correlated with body weight change but not with gastric ghrelin production.…”
Section: Discussionsupporting
confidence: 93%
“…There are contradictory reports on the influence of H. pylori eradication on ghrelin concentrations (25,26,29,48,49). In most studies, the follow-up was too short to see any change in BMI.…”
Section: Discussionmentioning
confidence: 99%
“…25,27 Recently, H. pylori eradication increased weight and decreased plasma ghrelin levels (but increased gastric levels) in men participating in a Japanese gastric cancer surveillance programme. 29 Large studies are now required to clarify the role of these peptides to mediate the influence of H. pylori eradication on BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Participants who tested positive for H. pylori with the UBT (using a standard test meal of citric acid and orange juice with a cutoff of Cd 13 3.5 per cm 3 ) 13 were randomised either to H. pylori eradication therapy (ranitidine bismuth citrate 400 mg and clarithromycin 500 mg twice daily for 2 weeks) or to placebo. Randomisation was stratified by gender and age (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)30-39, 40-49 and 50-59 years). Staff independent of the study prepared the randomisation sequence, which was generated by computer with a block size of 10.…”
Section: Methodsmentioning
confidence: 99%
“…Ghrelin levels increased, however, 12 weeks after successful H. pylori eradication (36)(37)(38). The density of ghrelinimmunoreactive cells was lower in the oxyntic mucosa of patients infected with H. pylori.…”
Section: Inflammatory and Infectious Gastrointestinal Diseasesmentioning
confidence: 99%